World Rowing Covid-19 Pandemic. Return to rowing training and avoiding risk of injury. - Wilson, Fiona (Fédération Internationale des Sociétés d'Aviron, 2020)
Following advice from FISA and local public health guidelines, rowing clubs are opening and boats are returning to the water. In our enthusiasm to return to normal life, attention needs to be given to the risk of sustaining an injury in this period.
Keywords: Rowing; Injuries